An integrated model highlighting information literacy and knowledge formation in information behaviour. Issue 3 (15th May 2017) - Ibenne, Samuel Kelechukwu; Simeonova, Boyka; Harrison, Janet; Hepworth, Mark
Abstract : Purpose: The purpose of this paper is to review key models of people's information behaviour (IB) exploring the integration of the concepts of information literacy (IL) and knowledge in their designs. Scholarly perspectives portray IL as providing individuals with capacity for good information practices that result in generating new knowledge. It is surprising that this important perspective is not reflected in the reviewed IB models. This paper contributes to the literature base by proposing a new model highlighting IL and knowledge as important concepts within the IB discourse. Design/methodology/approach: A discourse of the integration of IL and knowledge, which are integral factors, associated with IB, in selected IB models. Findings: Identifying a need for information and understanding its context is an IL attribute. IL underpins IB in providing awareness of information sources; how to search and use information appropriately for solving information needs and leveraging generated new knowledge. The generation of new knowledge results from using information, in a process that combines with sense-making and adaption. Correspondingly, the knowledge that develops, increases capability for sense-making and adaptation of information to suit various contexts of need, iteratively. Originality/value: A new model of IB; the causative and outcome factors of information behaviour (COFIB) is proposed. COFIB stresses that IL and knowledge are prominent factors within the general framework of people's IB. The model emphasises knowledge generation as the outcome of IB, applied in solving problems within specific contexts.